Implementasi Penggunaan Website Terintegrasi dalam Upaya Peningkatan Kualitas Manajemen dan Pemasaran Digital pada UMKM Payum Iwag di Papua Selatan - Arin Mantara Anggawirya; Damayanti Damayanti; Simon Siamsa; Rosalia Floriani; Nurul Istiqomah (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve production management quality and enhance the effectiveness of digital marketing for Payum Iwag, a micro, small, and medium enterprise (MSME) producing natural cosmetics based on coconut oil in South Papua. The program was implemented through participatory training and mentoring approaches. Program evaluation was conducted by directly involving the partner through interviews, pre- and post-test questionnaires, and observations of marketplace account performance. The results indicate significant improvements in management efficiency, production organization, as well as enhanced professional branding and expanded digital market reach. This implementation not only strengthened the competitiveness of Payum Iwag but also contributed to the achievement of the Sustainable Development Goals (SDGs), particularly in terms of gender equality, decent work, and industry innovation based on local wisdom. The outcomes of this program are expected to serve as a replicable model for the development of MSMEs utilizing local resources in the South Papua region.